Clinical Evaluation of 51 Patients with Cleft Lip and/or Palate in Social Work at Syariah Hospital. - Anggraini, Santi (Syntax Literate, 2024)
The study aims to evaluate the surgical outcomes, including post-operative complications, in patients undergoing cleft lip and palate surgery in social work. The study was conducted on 51 patients in three social work settings, with inclusion criteria of age over 3 months, weight over 10 pounds, and normal chest x-ray results. Patients with syndromic or cardiac abnormalities were excluded from the study. The surgery was performed by a team of oral and maxillofacial surgeons with a minimum of 2 years of surgical experience. The study found that post-operative complications were relatively rare and could be managed well. This study has important implications for improving the quality of healthcare services for patients with cleft lip and palate, as well as increasing public awareness of the importance of proper medical care for this condition.